Self-effective scientific reasoning? Differences between elementary and secondary school students - Kristin Nyberg; Susanne Koerber; Christopher Osterhaus (EARLI, 2022)
Although scientific reasoning is not a formal, independent school subject, it is an increasingly important skill, especially for student learning in science, technology, engineering, and mathematics (STEM) subjects. To promote scientific reasoning effectively, it is important to know its influencing factors. While cognitive influences have been investigated, affective-motivational factors, particularly self-efficacy, have rarely been considered in studies on scientific reasoning. To examine, for the first time, whether self-efficacy can be measured in a task-specific way and whether self-efficacy correlates with students' scientific reasoning performance, the study assessed performance in scientific reasoning and self-efficacy (academic and task-specific) in a sample of 140 fourth graders and 148 eighth graders. As expected, higher correlations emerged for task-specific self-efficacy in both grades. A hierarchical cluster analysis showed that the correlational patterns were not the same across grade levels, with differences in self-estimated performance prevailing between the two grade levels: The largest cluster in Grade 4 (41%) comprised children who significantly overestimated their performance, whereas the largest cluster in Grade 8 (39%) comprised students who gave a realistic estimate of their own performance in scientific reasoning. This cluster was not present in Grade 4. Additional clusters of students who overestimated or underestimated their performance emerged in both grades. The results support the conclusion that self-efficacy expectations are important to consider when fostering scientific reasoning, and the large number of elementary school students who overestimated their performance suggests that not all students might benefit from interventions targeted at increasing self-efficacy.